Study of The Temperature and Timing Roasting of Black Glutinous Rice and Robusta Beans on The Quality of Coffee Powder - Supermanto Supermanto; Suko Priyono; Sulvi Purwayantie; Nur Endah Saputri; Dzul Fadly; Dwi Ayuni (Journal of Health and Nutrition Research, 2022)
Coffee is a kind of drink that comes from the processing and extraction of coffee beans. In the production of coffee powder, the flavor is the essential quality because flavor affects consumer preferences. To produce a coffee drink that has a distinctive flavour, that is by combining robusta coffee beans and black glutinous rice. The purpose of this study was to determine the best treatment combination of temperature and roasting time of robusta coffee beans and black glutinous rice on the quality of the coffee powder. The research design used RAK which was arranged in a factorial manner of two factors, namely roasting temperatures of 190°C, 200°C, 210°C, and roasting times of 10, 15, and 20 minutes, to obtain 9 treatment combinations, 3 replicates. The research data were analyzed statistically by the ANOVA test, followed by the BNJ test. While the hedonic quality test is analyzed using the Friedman method. The Effectiveness Index test does determination of the best treatment. The best quality of coffee powder is produced at a temperature and roasting time of 200°C 20 minutes, namely the yield of 8.40%, the water content of 1.39%, ash content of 3.80%, the caffeine content of 1.33%, total antioxidants 71.87%, organoleptic characteristics, namely flavor 3.73 (strong), acidity 3.40 (quite sour), body/mouthfeel 3.67 (thick) and color 3.53 (black).